Proportionality, wrongs and equipoise for natural immunity exemptions: response to commentators - Pugh, Jonathan (Journal of medical ethics, 2022)
We would like to thank each of the commentators on our feature article for their thoughtful engagement with our arguments. All the commentaries raise important questions about our proposed justification for natural immunity exemptions to COVID-19 vaccine mandates. Thankfully, for some of the points raised, we can simply signal our agreement. For instance, Reiss is correct to highlight that our article did not address the important US-centric considerations she helpfully raises and fruitfully discusses. We also agree with Williams about the need to provide a clear rationale for mandates, and to obtain different kinds of data in support of possible policies. Unfortunately, we lack the space to engage with every one of the more critical comments raised in this rich set of commentaries; as such, in this response, we shall focus on a discussion of hybrid immunity, which underlies a number of different arguments evident in the commentaries, before concluding with some reflections responding to Lipsitch’s concern about the appropriate standard of proof in this context.